Uropatias fetais: avaliação dos critérios de diagnóstico morfológico e funcional - Alamanda Kfoury Pereira (1998)
Malformations of the fetal urinary tract account for approximately 20-30% of diagnosable structural abnormalities during the prenatal period. Among them, obstructive uropathy is the most common and are the main causes of renal failure in the second year of life. The posterior urethral valve is the main cause of urinary tract obstruction in neonates male, besides being the main cause of obstructive kidney disease in children, and its incidence 1 in 5000-8000 live births. OBJECTIVES: To investigate the relationship of biochemical and ultrasonographic markers of prenatal renal function and the occurrence of perinatal death, and the ability of these markers to predict postnatal renal function. METHODS: We selected from January 2008 to January 2013, 18 pregnant women whose fetuses had sonographic diagnosis of uropathy low and criteria for evaluation of renal function. Amniotic fluid volume, renal parenchyma, presence of fetal hydronephrosis, dilatation of the ureter and bladder, fetal urinary creatinine, 2-microglobulin, uromodulina, osmolarity and fetal urinary calcium were assessed, using mortality and postnatal renal function. RESULTS: Among the 18 selected cases, death occurred in 11 cases, and the survivors had their postnatal renal function assessed according to the protocol of the neonatology and pediatric nephrology service. There was no statistical significance of the parameters evaluated between the group developed demise and the survivor group. CONCLUSION: None of the analyzed parameters proved to be able to predict postnatal renal function and mortality.